2014
DOI: 10.1016/j.dnarep.2014.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling secrets of telomeres: One molecule at a time

Abstract: Telomeres play important roles in maintaining the stability of linear chromosomes. Telomere maintenance involves dynamic actions of multiple proteins interacting with long repetitive sequences and complex dynamic DNA structures, such as G-quadruplexes, T-loops and t-circles. Given the heterogeneity and complexity of telomeres, single-molecule approaches are essential to fully understand the structure-function relationships that govern telomere maintenance. In this review, we present a brief overview of the pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 138 publications
(184 reference statements)
0
21
0
Order By: Relevance
“…Furthermore, depletion of DNA damage–response factors can result in defective telomere maintenance; for example, studies have shown that cells lacking or deficient in certain helicases display telomere attrition and/or replication defects (Crabbe et al 2004; Sfeir et al 2009; Ghosh et al 2011). Human telomeric DNA includes 2–15 kb of tandem repeats of TTAGGG, plus aterminal 3′-protruding G-rich single-stranded DNA (ssDNA) tail greater than 100 nucleotides long (Lin et al 2014). The ssDNA tail folds back and invades the telomeric double-stranded DNA (dsDNA) forming a telomeric T-loop that is critical for telomere capping (Hanish et al 1994).…”
Section: Theories Of Agingmentioning
confidence: 99%
“…Furthermore, depletion of DNA damage–response factors can result in defective telomere maintenance; for example, studies have shown that cells lacking or deficient in certain helicases display telomere attrition and/or replication defects (Crabbe et al 2004; Sfeir et al 2009; Ghosh et al 2011). Human telomeric DNA includes 2–15 kb of tandem repeats of TTAGGG, plus aterminal 3′-protruding G-rich single-stranded DNA (ssDNA) tail greater than 100 nucleotides long (Lin et al 2014). The ssDNA tail folds back and invades the telomeric double-stranded DNA (dsDNA) forming a telomeric T-loop that is critical for telomere capping (Hanish et al 1994).…”
Section: Theories Of Agingmentioning
confidence: 99%
“…Telomeres, the tandem nucleotide repeats at chromosome ends, are markers of cellular replicative capacity, senescence, and biological aging [14]. Telomere length (TL) of newly engrafted cells shortens early after HCT as a consequence of the high degree of cellular replication needed to achieve engraftment [15-17].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, telomeres are markers of cellular replicative capacity, cellular senescence, and aging. 1 …”
Section: Introductionmentioning
confidence: 99%